Roles of GM-CSF in the Pathogenesis of Autoimmune Diseases: An Update - Lotfi, Noushin; Thome, Rodolfo; Rezaei, Nahid; Zhang, Guang-Xian; Rezaei, Abbas; Rostami, Abdolmohamad; Esmaeil, Nafiseh (Frontiers in Immunology, 2019)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) was first described as a growth factor that induces the differentiation and proliferation of myeloid progenitors in the bone marrow. GM-CSF also has an important cytokine effect in chronic inflammatory diseases by stimulating the activation and migration of myeloid cells to inflammation sites, promoting survival of target cells and stimulating the renewal of effector granulocytes and macrophages. Because of these pro-cellular effects, an imbalance in GM-CSF production/signaling may lead to harmful inflammatory conditions. In this context, GM-CSF has a pathogenic role in autoimmune diseases that are dependent on cellular immune responses such as multiple sclerosis (MS) and rheumatoid arthritis (RA). Conversely, a protective role has also been described in other autoimmune diseases where humoral responses are detrimental such as myasthenia graves (MG), Hashimoto’s thyroiditis, inflammatory bowel disease (IBD) and systemic lupus erythematosus (SLE). In this review, we aimed for a comprehensive analysis of literature data on the multiple roles of GM-CSF in autoimmue diseases and possible therapeutic strategies that target GM-CSF production.